Tracing The Khalwatiyah Order in The Tolitoli Regency Central Sulawesi - Saude Saude; Hamka Hamka; Kasmiati Kasmiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
This article discusses the history and process of transmitting the Khalwatiyah’s teachings in the Tolitoli Regency, Central Sulawesi. Researchers will examine problems with a socio-cultural-historical approach. The results indicate that The Khalwatiyah order that developed in Tolitoli is the Khalwatiyah Samman Order. This tariqa has entered Tolitoli since 1954, brought for the first time by Ambo Eko, a member of The Khalwatiyah order from South Sulawesi. This tariqa first spread in the village Bangkir located at The southernmost Tolitoli Regency. In the following period until the 1990s, this tariqa experienced significant development in the two districts, Galang and Lampasio, and then declined